The Influence of Service Quality on Satisfaction Public on Office Village Rangan, Kuaro District, Paser Regency - Ernawati Ernawati; Lisa Dayani; Bonney Arta Bontong; Diana Virgowaty; Masitah Masitah; Abdurahman Abdurahman (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine the service quality variables (X) consisting of reliability (X1 ) , responsiveness (X2 ) , assurance (X3), empathy ( X4 ), evidence ( X5 ), and reliability (X6). physique (X 5 ) influential in a way together to satisfaction community (Y) at the Rangan Village Office, and has a dominant influence on community satisfaction (Y). From results analysis regression linear multiple can equality function Y = −1.457 + 0.211X 1 + 0.104X 2 + 0.528X 3 + 0.375X 4 + 0.082X 5 . From The results show that the variables of reliability (X1 ) , responsiveness (X2 ) , assurance (X3 ) , empathy (X4 ) , and physical evidence (X5 ) have a positive influence on public satisfaction at the Rangan Village Office, Kuaro District, Paser Regency. Influence This Also explained with mark R 2 ( Coefficient Determination of 0.858, which means that the variables studied have an influence of 85.8% and the remaining 14.2% are influenced by other variables not included in this study. Correlation Coefficient (R), which describes the strength of the relationship between variable independent And variable dependent can seen on testing, which is 0.933. This means that there is a very strong relationship between the independent variables And dependent. Mark f count 68,890 > f table 2.39 And mark probability 0.000 < 0.05 indicates that the variables of reliability, responsiveness, assurance, empathy, and direct evidence have a simultaneous (together) effect on public satisfaction at the Rangan Village Office. Of the five variables, the empathy variable has a dominant effect, this is evidenced by the calculated t value of 3.596 > t table 2.00665.